2013
DOI: 10.3109/09638288.2013.797507
|View full text |Cite
|
Sign up to set email alerts
|

Self-management and adherence with exercise-based falls prevention programmes: a qualitative study to explore the views and experiences of older people and physiotherapists

Abstract: A focus on self-management support may provide the key to promoting uptake and adherence with an exercise-based falls prevention programme. Physiotherapists should move from being "experts" to "enablers" who use their professional knowledge and expertise to support older people at risk of falling to maintain optimum levels of health and independence. Implications for Rehabilitation Despite the established efficacy of exercise-based falls prevention programmes, their impact remains limited by low levels of upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 16 publications
3
74
1
Order By: Relevance
“…Child and colleagues describe "hierarchies of expertise" whereby healthcare professionals may assume that older people lack the competency to identify their own falls-risk [36]. Other work has demonstrated that older people place a higher emphasis on maintaining independence as opposed to falls-reduction when choosing to participate in an exercise-based fallsprevention programme [37]. Multifactorial falls-prevention interventions post stroke have not yet been shown to be effective [38].…”
Section: Discussionmentioning
confidence: 99%
“…Child and colleagues describe "hierarchies of expertise" whereby healthcare professionals may assume that older people lack the competency to identify their own falls-risk [36]. Other work has demonstrated that older people place a higher emphasis on maintaining independence as opposed to falls-reduction when choosing to participate in an exercise-based fallsprevention programme [37]. Multifactorial falls-prevention interventions post stroke have not yet been shown to be effective [38].…”
Section: Discussionmentioning
confidence: 99%
“…Pilot data has suggested benefit in PBC . There are real challenges, however, in getting CLD patients to accept that they are able to undertake exercise programmes and that these will benefit them …”
Section: Management Of Fatigue In Practicementioning
confidence: 99%
“…49 There are real challenges, however, in getting CLD patients to accept that they are able to undertake exercise programmes and that these will benefit them. [102][103][104] In many patients with liver disease and central fatigue, the degree and perpetuation of fatigue may be directly related to, and influenced by, a complex interaction of physiological, emotional, cognitive, behavioural and social factors, 8,10 with social dysfunction being integral to poor perceived QOL. 76 Targeting social dysfunction through improving social support networks and providing group therapy sessions to provide psychological support may prove beneficial, 24 although there has been little formal study in the area.…”
Section: Supportive Managementmentioning
confidence: 99%
“…Inpatient injurious falls that occur in US acute care hospitals are the most prevalent in-hospital adverse event, with rates as high as 21.4 falls per 1,000 patient days for older inpatients 714. Inpatients are at a greater risk of falling than those in the general population, mainly due to acute illness and being unfamiliar with the hospital environment 15–17.…”
Section: The Significance Of Fall-related Issues Among Hospitalized Omentioning
confidence: 99%
“…Robinson et al7 have highlighted a potential gap in clinical practice in which encounters between patients and clinicians should be (but have not been) a setting for new information exchange to promote patient empowerment and shared decision making. Clinical encounters via a Web-based program could be a venue for such exchanges, which might lead to better care outcomes (for example, to fewer inpatient injurious falls).…”
Section: Introductionmentioning
confidence: 99%